Culture dimensions and it capability influence on organizational intelligence of Libyan oil and gas companies / Hadya. S. Hawedi - S. Hawedi, Hadya. (2015)
Different groups have different culture. In Libya there are different ethnic culture and they are the main managers in the Libyan oil and gas companies. These ethnic groups include four main groups Arab, Berbers (Amazigh), Toubou and Tuaregs and each group has their own language, heritage, customs, values and beliefs even they have their own flag. The role of information technology capability in mediating the influence between cultural dimensions and organizational intelligence which ultimately contributes towards the performance of the companies are competitive advantage. The Libyan oil and gas companies are in dispersed locations, which necessitate an efficient and effective management system to improve their competitiveness, they need to pool resources in the organization to create organizational intelligence as to be competitive.Organizational intelligence is organizational practices which are influenced by cultural dimensions and IT capability. The objective of the study is to investigate how cultural dimensions influences organizational intelligence through IT capability in the Libyan oil and gas companies. These culture dimensions include resonant leadership, ethnic culture and organization culture. A quantitative research method based on survey questionnaire was used to collect numerical data that were statistically analysed using descriptive and inferential statistics based on Statistical Package of Social Science (SPSS) software and AMOS module. A total of 163 managers in the Libyan oil and gas companies were randomly selected as the respondents. The result of the analysis showed a significant relationship between cultural dimensions and organizational intelligence with a high correlation. Cultural sub dimensions of organizational culture also reflected a strong positive correlation. In other hand, the sub dimension ethnic culture and organizational intelligence were moderately correlated, the sub dimensions of resonant leadership the correlation was significant positive and strongly correlated. Finally, IT capability and organizational intelligence were moderately correlated. The result of the analysis for the regression of the mediation effect was conducted using two methods; conventional (Baron and Kenny) and contemporary (The Sobel Test and SEM), for an accurate result on how IT capability mediates between cultural dimensions and organizational intelligence. Result showed that resonant leadership was the significant predictors of organizational intelligence among the three cultural dimensions. IT capability, however partially mediates the influence between cultural dimensions and organizational intelligence. Cultural dimensions and IT capability are proven to be the Predictors of organizational intelligence. Cultural dimensions as whole influence IT capability. The sub dimension of cultural dimensions is resonant leadership which directly influence organizational intelligence, other cultural dimensions which are ethnic culture and organization culture influence organizational intelligence through IT capability. This study contributes towards new knowledge through the development of a predictor’s model of organizational intelligence in the context of Libyan oil and gas companies. The predictor’s model contributes towards practice through better decision making where the oil and gas companies management can decide on their investment for their companies in the future in order to increase their organizational intelligence.Moreover, this study, gives insights on how cultural dimensions influence organizational intelligence (OI).